A 10-day confinement to normobaric hypoxia impairs toe, but not finger temperature response during local cold stress. (February 2017) - Kounalakis, Stylianos N.; Keramidas, Michail E.; Amon, Mojca; Eiken, Ola; Mekjavic, Igor B.
Abstract: The study examined the effects of a 10-day normobaric hypoxic confinement on the finger and toe temperature responses to local cooling. Eight male lowlanders underwent a normoxic (NC) and, in a separate occasion, a normobaric hypoxic confinement (HC; FO2 : 0.154; simulated altitude 3400 m). Before and after each confinement, subjects immersed for 30 min their right hand and, in a different session, their right foot in 8 °C water, while breathing either room air (AIR) or a hypoxic gas mixture (HYPO). Throughout the cold-water immersion tests, thermal responses were monitored with thermocouples on fingers and toes. Neither confinement influenced thermal responses in the fingers during the AIR or HYPO test. In the foot, by contrast, HC, but not NC, reduced the average toe temperature by 1.5 °C (p=0.03), both during the AIR and HYPO test. We therefore conclude that a 10-day confinement to normobaric hypoxia per se augments cold-induced vasoconstriction in the toes, but not in the fingers. The mechanism underlying this dissimilarity remains to be established. Highlights: The study examined the effect of prolonged hypoxia exposure on local cold tolerance. Cold-induced vasoconstriction in the toes is augmented after acclimatization. The latter response is not observed in the fingers. These responses to a hypoxic stimulus are not homogeneous between fingers and toes.